Rapid measurements of curcumin from complex samples coupled with magnetic biocompatibility molecularly imprinted polymer using electrochemical detection. Issue 6 (24th February 2020) - Li, Wei; Jiang, Zhuang‐Fei; Tan, Ling; Wang, Shu‐Xian; Wang, Chong‐Zhi; Zhang, Jia‐Wei; Zhou, Lian‐Di; Zhang, Qi‐Hui; Yuan, Chun‐Su
Abstract: Curcumin widely exists in food, and rapid selective and accurate detection of curcumin have great significance in chemical industry. In this experiment, a new magnetic biocompatibility molecularly imprinted polymer was prepared with nontoxic and biocompatible Zein to adsorb curcumin selectively. The polymer has high biocompatibility, good adsorption capacity, and specific adsorption for curcumin. Combined with portable electrochemical workstations, the polymer can be used to detect curcumin rapidly and cost‐effectively. Using curcumin as a template and Zein as the crosslinking agent, the polymers were synthesized on the surface of Fe3 O4 particles for solid phase extraction. The experimental results showed that the polymer reached large adsorption capacity (32.12 mg/g) with fast kinetics (20 min). The adsorption characteristic of the polymer followed the Langmuir isotherm and pseudo‐second‐order kinetic models. Hexacyanoferrate was used as electrochemical probe to generate signals, and the linear range was 5–200 µg/mL for measuring curcumin. The experimental analysis showed that the polymer was an ideal material for selective accumulation of curcumin from complex samples. This approach has been successfully applied to the determination of curcumin in food samples with electrochemical detection, indicating that this is a feasible and practical technique.